Environmentally benign approach towards C–S cross-coupling reaction by organo-copper(II) complex - Singha, Rabindranath; Chettri, Sailesh; Brahman, Dhiraj; Sinha, Biswajit; Ghosh, Pranab (Molecular diversity, 2022)
C–S cross-coupling reaction in water giving an excellent yield of the desired C–S coupled product by using a newly developed Bis[2-(4,5-diphenyl-1 H -imidazol-2-yl)-4-nitrophenolato] copper(II) dehydrate complex as catalyst. Although it was the first report of the synthesis of such a novel organo-copper complex from our laboratory, its potential catalytic application was not tested so far. Keeping this in mind and based on our anticipation, we developed a greener route for the C–S coupling reaction. The result is very interesting and comprises the subject matter of this report. Graphic abstract